Desenvolvimento de um sistema microfluídico alternativo à base de fios têxteis para aplicações eletroanalíticas - Oliveira, Ana Clara Maia (2021)
The integration of thread-based microfluidic devices with electrochemical detection shows advantages such as simplicity, ease of miniaturization, low sample consumption, low cost, and numerous possibilities of configurations. However, the fluid evaporation and difficulty in maintaining a constant flow are some limitations of these systems. In addition, many of these systems are completely disposable after studies. Thus, in this work, it is proposed the development of an alternative thread-based microfluidic device manufactured with low-cost materials and coupled to amperometric detection. Syringes were used as inlet and outlet reservoirs, which were fixed on a poly(methyl methacrylate) plate. The textile threads were inserted into polyethylene tubes, resulting in some advantages such as decreased evaporation of the solvent from carrier solution, making the system more robust and less susceptible to contamination. Three platinum wires were coupled to the thread/tube set, and they were used as pseudo-reference, work, and auxiliary electrodes. Cotton was added to the outlet reservoir, favoring the absorbing capacity of the system, increasing capillary strength, in addition to allowing, after the measurements, the device to be reused only by changing cotton at the outlet reservoir. Comparative studies between two types of textile thread (gauze and string) were carried out and the ferrocyanide was employed for the optimization of the main parameters of the system: dimensions of the inlet and outlet reservoirs, the distance between injection and detector, volume, and a maximum number of injections and flow rate. To evaluate the analytical potential of the device, dopamine, hydrogen peroxide, and TBHQ were used as model analytes, being obtained adequate linearities (R2 > 0.99) and values of detection limits compatible with those reported in the literature. In the last stage, the microfluidic system was used for the determination of nitrite in artificial saliva samples. Addition and recovery studies were conducted for a concentration range of 30-100 µmol L-1 , and recovery values close to 100% (87.9-111%) were obtained. Thus, this work describes a promising, low-cost analytical tool that circumvents some limitations indicated in the literature, presenting the potential for analysis in the field, since it precludes the use of external pumps, drastically reducing the generation of waste, and has satisfactory analytical performance.